Generalizability of HFA-PEFF and H2FPEF Diagnostic Algorithms and Associations With Heart Failure Indices and Proteomic Biomarkers: Insights From PROMIS-HFpEF - Faxen U. L.; Venkateshvaran Ashwin; Shah Sanjiv J.; Lam Carolyn S. P.; Svedlund Sara; Saraste Antti; Beussink-Nelson Lauren; Lagerstrom Fermer Maria; Gan Li-Ming; Hage Camilla; Lund Lars H. (Elsevier B.V., 2022)
Background
Diagnosing heart failure with preserved ejection fraction (HFpEF) remains challenging. We aimed to evaluate the generalizability of the HFA-PEFF (Heart Failure Association Pre-test assessment, Echocardiography & natriuretic peptide, Functional testing, Final etiology) and weighted H2FPEF (Heavy, 2 or more Hypertensive drugs, atrial Fibrillation, Pulmonary hypertension, Elder age > 60, elevated Filling pressures) diagnostic algorithms and associations with HF severity, coronary microvascular dysfunction and proteomic biomarkers.
Methods and Results
Diagnostic likelihood of HFpEF was calculated in the prospective, multinational PROMIS-HFpEF (Prevalence of microvascular dysfunction in HFpEF) cohort using current European Society of Cardiology recommendations, HFA-PEFF and H2FPEF algorithms. Associations between the 2 algorithms and left atrial function, Doppler-based coronary flow reserve, 6-minute walk test, quality of life, and proteomic biomarkers were investigated. Of 181 patients with an EF of ≥50%, 129 (71%) and 94 (52%) fulfilled criteria for high likelihood HFpEF as per HFA-PEFF and H2FPEF, and 28% and 46% were classified as intermediate likelihood, requiring additional hemodynamic testing. High likelihood HFpEF patients were older with higher prevalence of atrial fibrillation and lower global longitudinal strain and left atrial reservoir strain (P < .001 for all variables). left atrial reservoir strain and global longitudinal strain were inversely associated with both HFA-PEFF and H2FPEF scores (TauB = –0.35 and –0.46 and –0.21 and –0.31; P < .001 for all). There were no associations between scoring and 6-minute walk test, quality of life, and coronary flow reserve. Both scores were associated with biomarkers related to inflammation, oxidative stress, and fibrosis.
Conclusions
Although the HFA-PEFF and H2FPEF scores were associated with measures of HF severity and biomarkers related to HFpEF, they demonstrated a modest and differential ability to identify HFpEF noninvasively, necessitating additional functional testing to confirm the diagnosis.